Pediatric systemic lupus erythematosus with lupus anticoagulant hypoprothrombinemia syndrome—A case series with review of literature. (April 2021) - Kocheril, Anu Punnen; Vettiyil, George Ipe; George, Anish Sam; Shah, Sonam; Geevar, Tulasi; Dave, Rutvi Gautam; T, Sathish Kumar
Introduction: Lupus anticoagulant hypoprothrombinemia syndrome (LAHPS) is a rare phenomenon that leads to concomitant thrombosis and hemorrhage in children with SLE. LAHPS in pediatric SLE (pSLE) has a protracted course requiring long-term immunosuppressive therapy. Due to the rarity of this syndrome and paucity of reported cases, there is lack of standardized management. We herewith report 5 children with pSLE with LAHPS. Methodology: We retrospectively reviewed clinical features, laboratory features, treatment and outcome for 5 children with lupus anticoagulant hypoprothrombinemia syndrome with SLE and a review of literature of similar cases published. Results: Mean age of presentation was 10.2 ± 2.38 years (mean ± SD) and female to male ratio was 4:1. All children presented with mild to severe bleeding manifestations like gum bleed, epistaxis, hematuria, menorrhagia and subarachnoid bleed. Coagulation profile revealed prolonged PT and aPTT, with low prothrombin levels and positive Lupus anticoagulant in all children. Mixing studies were characteristic in these children. On comparing laboratory parameters majority had low C3, C4 levels, ANA and anti-DsDNA antibody positivity and three children had anticardiolipin positivity. One child had lupus nephritis along with LAHPS at presentation. All responded well to steroids and supportive measures. Conclusion: High index of suspicion is needed when child with lupus presents with bleeding manifestations for early diagnosis and treatment.